European registry of type A aortic dissection (ERTAAD) - rationale, design and definition criteria - Biancari, Fausto; Mariscalco, Giovanni; Yusuff, Hakeem; Tsang, Geoffrey; Luthra, Suvitesh; Onorati, Francesco; Francica, Alessandra; Rossetti, Cecilia; Perrotti, Andrea; Chocron, Sidney; Fiore, Antonio; Folliguet, Thierry; et al. (Journal of cardiothoracic surgery, 2021)
BACKGROUND: Acute Stanford type A aortic dissection (TAAD) is a life-threatening condition. Surgery is usually performed as a salvage procedure and is associated with significant postoperative early mortality and morbidity. Understanding the patient's conditions and treatment strategies which are associated with these adverse events is essential for an appropriate management of acute TAAD. METHODS: Nineteen centers of cardiac surgery from seven European countries have collaborated to create a multicentre observational registry (ERTAAD), which will enroll consecutive patients who underwent surgery for acute TAAD from January 2005 to March 2021. Analysis of the impact of patient's comorbidities, conditions at referral, surgical strategies and perioperative treatment on the early and late adverse events will be performed. The investigators have developed a classification of the urgency of the procedure based on the severity of preoperative hemodynamic conditions and malperfusion secondary to acute TAAD. The primary clinical outcomes will be in-hospital mortality, late mortality and reoperations on the aorta. Secondary outcomes will be stroke, acute kidney injury, surgical site infection, reoperation for bleeding, blood transfusion and length of stay in the intensive care unit. DISCUSSION: The analysis of this multicentre registry will allow conclusive results on the prognostic importance of critical preoperative conditions and the value of different treatment strategies to reduce the risk of early adverse events after surgery for acute TAAD. This registry is expected to provide insights into the long-term durability of different strategies of surgical repair for TAAD. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT04831073 .
Keywords: senioři; klinické protokoly; Aortic Dissection; senioři nad 80 let; reoperace; Retrospective Studies; komorbidita; Europe; transplantace cév; Prognosis; Evropa; Middle Aged; registrace; mužské pohlaví; Stanford type A; Adult; Postoperative Complications; Registries; mortalita v nemocnicích; Reoperation; Clinical Protocols; Aged, 80 and over; Aortic arch; Vascular Grafting; ženské pohlaví; prognóza; retrospektivní studie; Humans; Ascending aorta; Comorbidity; Emergency; lidé středního věku; Hospital Mortality; rizikové faktory; Aortic Aneurysm; aortální aneurysma; dospělí; Aortic dissection; Female; disekce aorty; Aged; Risk Factors; výzkumný projekt; Research Design; pooperační komplikace; lidé; Male